The Effectiveness of Policy Implementation of Sultan Syarif Hasyim Forest Park in Riau Province - Nur Suhada; Hariadi Kartodihardjo; Dudung Darusman (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
Since it was established as the Sultan Syarif Hasyim Forest Park in 1999, the implementation of policies management has not been effective due to increase of land tenure issue which has caused deforestation to become oil palm planation. The objective of this study was to formulate a strategy to increase the effectiveness of SSH Forest Park policies management. The SSH Forest Park policy management incapability of facts and implementation were influenced by high political and economic interests, participation and low level of community empowerment, human resources competencies and the low responsiveness of target groups. Those are due to the ineffectiveness of the policy content and policy environment implementation so to improve the implementation of the policy the government needs to streamline the contents of the policy and policy environment implementation. This also needs to be supported by reforms and governance arrangements to address policy gaps and implementation in the field such as strengthening and optimizing protection, agroforestry and ecotourism partnerships, zoning integration, improving communication for targeted groups in terms of implementation effectiveness of SSH management policies. Keywords: effectiveness, forest park SSH, implementation, land tenure, policy